Unusual gross presentation of sarcocystis-like pectoral muscle lymphoma attributed to Marek’s disease in a backyard chicken - Gornatti Churria, Carlos Daniel (2017)
Marekʼs disease–induced lymphomas of skeletal muscle are rarely reported in chickens. Three mixed-breed, adult backyard chickens, which belonged to a flock with a previous history of anorexia, depression, ruffled feathers, whitish diarrhea, weight loss and death, were submitted for postmortem examination and diagnostic testing. Grossly, 2 birds had moderate pectoral atrophy, whereas the remaining chicken had numerous white, rice-grain sized foci distributed throughout the pectoral musculature. Severe proventricular wall thickening was observed in all 3 chickens and moderate intestinal Ascaridia spp. parasitism was diagnosed in 2 of the birds. Microscopically, the peripheral nerves, cerebrum, proventriculus, and pectoral musculature were severely infiltrated by mononuclear pleomorphic cells. Formalin-fixed, paraffin-embedded tissues from all 3 chickens were polymerase chain reaction positive for Marekʼs disease virus. A diagnosis of Marekʼs disease was based on the combined necropsy, histopathology, and polymerase chain reaction findings. This article describes the unusual gross presentation of rice-grain sized and shaped lymphomas in the pectoral musculature of chickens caused by Marekʼs disease.